An effective spray drift-reducing method for a plant-protection unmanned aerial vehicle - Chen, Yayong; Hou, Chaojun; Tang, Yu; Zhuang, Jiajun; Lin, Jintian; Luo, Shaoming (International Journal of Agricultural and Biological Engineering, 2019)
A spraying system for a plant-protection unmanned aerial vehicle (UAV) was designed to reduce spray drift. A custom low-speed wind tunnel was constructed to generate a wind speed ranging from 0 to 5.92 m/s. The results showed that the wind speed was attenuated with an increase in distance. To compensate for the attenuation, a linear-fitting model was adopted. Then, the relationship between the spraying pressure and atomization rate was analyzed, and a fuzzy algorithm was adopted to adjust the spraying angle and pressure according to the wind speed and its changing rate. Finally, an evaluation of the proposed system in the compensated wind tunnel was conducted, and the drift distance was reduced by 33.7% compared with the system without adjustment of the spraying angle and pressure.Keywords: plant-protection UAV, spray drift, spraying pressure, spraying angle, fuzzy algorithmDOI: 10.25165/j.ijabe.20191205.4289Citation: Chen Y Y, Hou C J, Tang Y, Zhuang J J, Lin J T, Luo S M. An effective spray drift-reducing method for a plant-protection unmanned aerial vehicle. Int J Agric & Biol Eng, 2019; 12(5): 14–20.